Protegrin-1 inhibits Dengue NS2B-NS3 serine protease and viral replication in MK2 Cells - Rothan, H.A.; Abdulrahman, A.Y.; Sasikumer, P.G.; Othman, S.; Abd Rahman, N.; Yusof, R. (2012)
Dengue diseases have an economic as well as social burden worldwide. In this study, the antiviral activity of protegrin-1 (PG-1, RGGRLCYCRRRFCVCVGR) peptide towards dengue NS2B-NS3pro and viral replication in Rhesus monkey kidney (MK2) cells was investigated. The peptide PG-1 was synthesized by solid-phase peptide synthesis, and disulphide bonds formation followed by peptide purification was confirmed by LC-MS and RPHPLC. Dengue NS2B-NS3pro was produced as a single-chain recombinant protein in E. coli. The NS2B-NS3pro assay was carried out by measuring the florescence emission of catalyzed substrate. Real-time PCR was used to evaluate the inhibition potential of PG-1 towards dengue serotype-2 (DENV-2) replication in MK2 cells. The results showed that PG-1 inhibited dengue NS2B-NS3pro at IC50 of 11.7 mu M. The graded concentrations of PG-1 at nontoxic range were able to reduce viral replication significantly (P < 0.001) at 24, 48, and 72 hrs after viral infection. However, the percentage of inhibition was significantly (P < 0.01) higher at 24 hrs compared to 48 and 72 hrs. These data show promising therapeutic potential of PG-1 against dengue infection, hence it warrants further analysis and improvement of the peptide features as a prospective starting point for consideration in designing attractive dengue virus inhibitors.